HIV related risks among Croatian migrant workers 2004-2006 - Štulhofer, Aleksandar (Array, 2008)
Two waves of a cross-sectional research study focusing on HIV-related risks in a population of migrant workers were carried out in 2004 and 2006. The research focused on changes in HIV knowledge, beliefs about condom use and risk-taking behaviours. The study included 552 migrant workers in 2004 and 671 in 2006. Using a self-administered questionnaire, data was collected in occupational health offices in nine cities during the process of medical examination required for licensing. Three major changes were observed in the 2004-2006 period. HIV knowledge improved and an increase in condom use at last sexual intercourse with casual partner and at last anal sex was reported. The changes in condom use were observed only among participants who were married or in a relationship. No significant change was recorded in the rates of HIV testing. In 2006, marital status, occupation, beliefs about condom use and personal HIV concerns were found significant predictors of HIV-related behavioural change. Overall, the findings suggest a small reduction in HIV-related sexual risks among migrant workers in Croatia.